Experimental and theoretical investigations on the EPR parameters and molecular orbital bonding coefficients of VO2+ ions in BTTB glasses. Issue 17 (13th June 2018) - Srinivas, B.; Hameed, Abdul; Vijaya Kumar, R.; Narasimha Chary, M.; Shareefuddin, Md.
Abstract: The effect of the spin probe VO 2+ in 15BaO–15TeO2 –10TiO2 -(60- x ) B2 O3 – x V2 O5 ( x  = 0.2, 0.4, 0.6, 0.8 mol %) glasses has been studied by employing Electron Paramagnetic Resonance (EPR) and optical absorption spectroscopic techniques. The observed EPR spectra of VO 2+ ions were attributed on the basis of well-known spin-Hamiltonian of C4V symmetry. The simulated EPR spectra for VO 2+ ions in the present glass system were drawn using Easy spin software. Both the experimental and simulated spectra were found to be in good agreement with each other. The optical absorption spectra exhibited three d–d transition bands due to crystal and tetragonal fields of VO 2+ ions. These bands were assigned to 2 B 2 g → 2 E g, 2 B 2 g → 2 B 1 g and 2 B 2 g → 2 A 1 g transitions. The crystal field parameters Dq, Ds and Dt values are calculated. From the EPR and optical data, the molecular bonding coefficients were evaluated. Employing the higher order perturbation formulae of the g factors for 3d 1 ion under tetragonally compressed octahedral fields, theoretical studies were carried out. The spin-Hamiltonian parameters and obtained from both the experimental and theoretical methods were in good agreement with each other.